2016
DOI: 10.1186/s13068-015-0406-9
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-mediated microalgae harvesting method for efficient biofuel production

Abstract: BackgroundProduction of biofuels from microalgae has been recognized to be a promising route for a sustainable energy supply. However, the microalgae harvesting process is a bottleneck for industrialization because it is energy intensive. Thus, by displaying interactive protein factors on the cell wall, oleaginous microalgae can acquire the auto- and controllable-flocculation function, yielding smarter and energy-efficient harvesting.ResultsTowards this goal, we established a cell-surface display system using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This marine diatom accumulates a large amount of storage lipids in the form of triacylglycerol (TAG) [ 22 ]. Multiomics studies of this diatom have been conducted [ 22 , 23 , 24 ], and these investigations provided useful targets for genetic manipulation to further improve the efficiency of biofuel production [ 25 , 26 ]. The outdoor cultivation study conducted at Kitakyushu (33°92’73”N, 130°74’15”E) in Japan revealed that this diatom showed steady growth in raceway- and column-type bioreactors without temperature control from spring to autumn seasons (April–November).…”
Section: Introductionmentioning
confidence: 99%
“…This marine diatom accumulates a large amount of storage lipids in the form of triacylglycerol (TAG) [ 22 ]. Multiomics studies of this diatom have been conducted [ 22 , 23 , 24 ], and these investigations provided useful targets for genetic manipulation to further improve the efficiency of biofuel production [ 25 , 26 ]. The outdoor cultivation study conducted at Kitakyushu (33°92’73”N, 130°74’15”E) in Japan revealed that this diatom showed steady growth in raceway- and column-type bioreactors without temperature control from spring to autumn seasons (April–November).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we employed frustulin, which is known to localize at the surface of the silica cell walls, as an anchor molecule for peptide display and potentially providing an active interface for TiO 2 nucleation. There are several other types of silica cell wall-associated proteins including silaffin, which are embedded in the silica, and cingulin, which are specifically localized at the girdle bands (lateral face) of the diatom cells .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Genetically Engineered Diatom Cell Walls for Enhanced Titania Deposition. In our previous study, 49 a cell surface display system for F. solaris was established by engineering a silica cell wall-associated protein, frustulin1. For a further enhancement of the deposition of titanium species on the silica cell walls, a titanium-associated peptide (RKKRKKRKKRKKGGGW, referred to as dTi1 peptide), designed by Dickerson et al, 42 was displayed on the surface of the silica cell walls with frustulin1 as the anchor, a green fluorescent protein marker, and a (GGGGS) 3 linker (Figure 3A, see also the experimental section in the Supporting Information).…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…S8C), demonstrating a lack of specific interactions between the cells of the Z Taq and antiZ Taq strains. Previous studies have shown that the time of contact between interacting partners is an important parameter to consider (50). To test this, the PilA1-Z Taq ΔpilT1 and PilA1-antiZ Taq ΔpilT1 strains were cultivated together and then analyzed for improved sedimentation, in comparison to the strains grown individually.…”
Section: Display Of Polymerizing Affibodies For Affinity-drivenmentioning
confidence: 99%